INVESTIGATION OF GRANULAR NATURAL STONE MATERIALS AS PHOTOTHERMAL ABSORBERS FOR SUSTAINABLE AND ENVIRONMENTALLY FRIENDLY ENERGY HARVESTING - Sarifudin, Alfan; Yaningsih, Indri; Kristiawan, Budi; Wibawa, Aditya; Miyazaki, Takahiko; Thu, Kyaw; Silitonga, Arridina Susan; Ong, Hwai Chyuan (Journal of Applied Engineering Science, 2024)
The development of cost-effective and environmentally friendly solar thermal technologies that deliver high performance poses several challenges, where the collector and absorber components play a pivotal role. This research addresses these issues by investigating enhanced temperature generation using a 30 cm × 30 cm Fresnel lens collector under solar illumination from a xenon lamp. Natural stone materials (andesite, coal, and pumice), characterized by granular structures with an average diameter of 1.68–2.00 mm, were selected because of their abundance and eco-friendliness. This research is focused on evaluating the effect of Fresnel lens on temperature generation performance. Two types of temperature generation tests were carried out: wet tests (where the natural stone materials were immersed in distilled water) and dry tests (where the natural stone materials were used in dry conditions). The morphologies of the natural stone materials were examined using an optical microscope and scanning electron microscope. Furthermore, the optical properties of the natural stone materials were analyzed using an ultraviolet–visible (UV–VIS) spectrophotometer. The findings revealed that there were significant improvements in the photothermal absorber performance with the use of a Fresnel lens in dry tests, where the highest temperature was achieved for coal (103.25 °C), followed by andesite (89.00 °C) and pumice (73.00 °C). The impurities varied between the materials, where the impurities were most dominant for pumice while coal was more uniform. Further examination using scanning electron microscope showed that all materials had light-trapping structures in the form of rough surfaces, pores, and crack gaps. Andesite was dominated by rough surfaces, while coal and pumice were dominated by crack gaps and pores, respectively. However, based on the UV–VIS spectrophotometric results, there were no correlations between the optical properties (absorbance, reflectance, and transmittance) and temperature achieved by the photothermal absorber materials. This research demonstrates the potential of using natural stone materials as photothermal absorbers in combination with a Fresnel lens collector for low-to-medium temperature solar thermal applications.